The non-innocent nature of graphene oxide as a theranostic platform for biomedical applications and its reactivity towards metal-based anticancer drugs1. Issue 93 (11th October 2015) - Mokdad, Audrey; Dimos, Konstantinos; Zoppellaro, Giorgio; Tucek, Jiri; Perman, Jason A.; Malina, Ondrej; Andersson, K. Kristoffer; Ramanatha Datta, Kasibhatta Kumara; Froning, Jens Peter; Zboril, Radek
<x xml:space="preserve">Abstract</x> The self-assembly process of a mononuclear iron(ii) complex as anticancer agent with graphene oxide (GO) unveils the ability of GO to oxidize the metal drug.